Effect of Anodal Transcranial Direct Current Stimulation to Flexor Digitorum Superficialis Muscle Activities in Stroke Subjects - Ana Mursyida; Imam Subadi; Reni Hendrarati Masduchi (Surabaya Physical Medicine and Rehabilitation Journal, 2022)
Background: Stroke is the main causes of upper extremity weakness that may affect physicalindependency resulting in long-term disability. Previous studies showed that A-tDCS can improve neurological damage. A-tDCS causes depolarization and inducesbrainsynapticplasticity in strokesubjects.Aim: To analyze the effect of Anodal-tDCS to the flexor digitorum superficialis muscles activities in stroke subjects.Material and Methods: This experimental study was conducted from April to September 2020. Eightpatients who suffered first attack ischemic stroke, aged 40 to 70 years old, were recruited from PMR out patient clinic at Dr.Soetomo General Hospital Surabaya. Subjects were randomized in to experimental and control group. The control group was given occupational therapy for 30 minutes, while the experimental group was given A-tDCS with intensity 2 mA for 20 minutes and occupational therapy for 30 minutes in 5 consecutive days. Measurement of FDS muscle activities using sEMG were performed before and after interventionin both groups. Results: There was an increase of FDS muscles activities after treatment incontrol group (p=0,048) while there was no similar result in treatment group (p=0,188). Thechangeofmuscles activities was notdifferent betweengroups(p=0,974).Conclusion: tDCS provides no significant benefit in terms of muscle activities in patients with stroke. Small number of samples and other several factors might limit the significancy of current study. Further study is needed to determine the benefit of A-tDCS as a rehabilitation modality in patient with stroke.